Pembelajaran Terintegrasi STEAM berbasis Kearifan Lokal: Strategi Signifikan dalam Meningkatkan 4 Cs di Abad 21 - Naela Khusna Faela Shufa; Tito Pangesti Adji (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to explain the impact of implementing integrated STEAM learning based on Local Wisdom in improving the 4 Cs in the 21st Century. The research method used is a case study in an elementary school, with data collection through classroom observations, interviews with teachers and students, as well as analysis of the results. learning before and after implementing STEAM learning. The data in this study were analyzed using qualitative descriptive analysis. The research results show that integrated STEAM learning based on local wisdom helps elementary school students achieve 21st century skills such as critical thinking, creativity, collaboration and communication, with an average increase of over 3,500 in each skill category. Furthermore, contextual learning by integrating local wisdom in learning makes learning more meaningful. The implications of this research provide an important contribution to the development of meaningful learning management in elementary schools to equip students with the skills needed in the future.